2003
DOI: 10.1520/jfs2002030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the DNA Stability of Forensic Markers Used in Betel-Quid Chewers' Oral Swab Samples and Oral Cancerous Specimens: Implications for Forensic Application

Abstract: Chewed betel-quid (BQ) residues are often considered vital biological evidence at crime scenes, since the human DNA extracted from the residues is actually from buccal epithelial cells and can be associated with suspects. BQ-chewing is also a risk factor for oral diseases and/or cancers. Archived medical oral-specimens can be used to identify specific individuals under adverse conditions, although STR markers are known to be unstable in various tumor tissues. This study evaluates the DNA stability of forensic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This leads to the assumption that the reliability of allelic typing with commercially available multiplex kits common in forensic analysis (comprising STR loci) may be questionable. [11,12] and Pai et al detected LOH and MSI in 21 and 17% of oral cancer samples [13], but in an additional study from this working group concerning HLA-DQA1/PM loci only one mutation was found [14]. Very recently, Vauhkonen et al described instability in STRs in two-third of gastrointestinal carcinomas [15].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the assumption that the reliability of allelic typing with commercially available multiplex kits common in forensic analysis (comprising STR loci) may be questionable. [11,12] and Pai et al detected LOH and MSI in 21 and 17% of oral cancer samples [13], but in an additional study from this working group concerning HLA-DQA1/PM loci only one mutation was found [14]. Very recently, Vauhkonen et al described instability in STRs in two-third of gastrointestinal carcinomas [15].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that this sporadic finding represents microsatellite instability, which is a feature of many malignant tumors. [16][17][18][19][20][21][22][23][24] It came as a surprise to us that the source of contamination (an ovarian papillary serous adenocarcinoma) had been processed as long as 6 days before the specimen that became contaminated. We suspect that tiny fragments of this friable tumor had escaped through the fenestrations in the cassettes in which it was being processed; that these fragments were retained in the fluid reservoirs in the processor, which had not been cleaned and refilled in the interim; and that, in due course, one such fragment found its way through the fenestrations into the cassette containing our patient's cervical polyp and then was embedded with it.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from issues dealing with medically derived biopsy samples, another potential problem area has been highlighted in a number of publications addressing the collection of buccal cell reference samples from individuals diagnosed with oral cancers, in particular, betel-quid (BQ) chewers in Taiwanese populations [19,20]. Despite its association with oral diseases and cancers, the practice of BQ chewing is particularly popular throughout Taiwan, to the extent that chewed BQ residues are often recovered as a potential DNA source from many crime scenes [19].…”
Section: Forensic Microsatellitesmentioning
confidence: 99%
“…Despite its association with oral diseases and cancers, the practice of BQ chewing is particularly popular throughout Taiwan, to the extent that chewed BQ residues are often recovered as a potential DNA source from many crime scenes [19]. A detailed study was undertaken to assess the potential for errors in STR DNA proWles produced from buccal swabs collected from oral cancer patients.…”
Section: Forensic Microsatellitesmentioning
confidence: 99%